The Use of Lokal Wisdom-Based Media To Improve Critical Thinking - Mulatsih, Dhina; Yamtinah, Sri; Matsuri, Matsuri (Postgraduate, University of Mataram, 2023)
The purpose of this study was to determine the effect of guided inquiry based on local wisdom on students' practical thinking skillsÂ in grade IV elementary school. The type of research used is the experiment with the Pretest Posttest Only Group Design. The instruments used are tests and observations and documentation. The results of this study indicate that the model of guided inquiry based on local wisdom is effective for improving critical thinking skills in the theme of sciences class IV elementary school rather than guided inquiry models. This is evidenced by the results of the mean value of guided inquiry models based on local wisdom rather than guided inquiry models (76.55 > 67.94), there is a significant effect of students' critical thinking skills between the model of guided inquiry based on local wisdom and the guided inquiry model. This is evidenced by the results of t count > t table (2.757 > 2.002) and smaller significance value with a significance level of 5% (p = 0.010 > 0.05).